Characteristics of older people in an inpatient haematology unit: A descriptive study. (10th July 2018) - Thillainadesan, Janani; Ng, Lisa; Cunningham, Ilona; Wong Doo, Nicole; Naganathan, Vasi
Abstract : Objective: To characterise older inpatients in a haematology unit. Methods: Hospital case‐mix data of haematology separations of all ages (n = 7419) and more extensive data restricted to older patients (age ≥75 years, n = 1025) were evaluated. Results: From 2000 to 2014, there was a 200% increase in those aged ≥85 years who were more likely to have a geriatric syndrome as the principal diagnosis (P < 0.05), have delirium (P < 0.05), receive less intensive treatment (P < 0.001) and be discharged to a nursing home (P < 0.001). Compared to younger inpatients, those aged ≥75 years were more likely to be emergency admissions (48% vs 37%, P < 0.001) and die during the admission (8% vs 4%, P < 0.001). Conclusion: Haematologists care for older inpatients who are complex with multidisciplinary health service needs. There may be value in conducting comprehensive geriatric assessments in this setting.